SCHOOL HEALTH PROGRAMME FOR STUDENTS, TEACHERS, AND PARENTS IN ELEMENTARY TO IMPROVE ORAL HEALTH KNOWLEDGE IN MALANG - Feni Istikharoh; Trining Widodorini; Yuanita Lely Rahmawati; Sinta Candra Wardani; Ranny Rachmawati; Meilia Aquina Hakim; Citra Insany Irgananda (Caring : Jurnal Pengabdian Masyarakat, 2023)
Dental and oral health has an important role in supporting the health of the human body. Diseases and disorders of the teeth in school-age children between 7-15 years are disturbances in growth and development. However, many factors still influence the occurrence of dental and oral problems. One of them is the lack of attention and knowledge. At the age of children, parents and teachers have an important role in guiding, providing understanding, reminding and providing facilities to maintain healthy teeth and mouth. Therefore, all three of them need to know to underlie the formation of behaviors that support children adopting a healthy lifestyle. Based on these conditions, we conducted community service to increase this knowledge through the School Health Program, which was implemented in 7 elementary schools in Malang City. In this activity, education was carried out for students, parents and teachers with a total of 325 participants. The results of this program show an increase in knowledge by students, teachers and parents. The knowledge conveyed included basic dental care recommendations such as brushing teeth twice a day with fluoride toothpaste, managing good eating habits, staying away from bad habits that damage teeth and preventing dental caries as early as possible. After completing this activity, participants can adopt a healthy lifestyle to prevent problems with their teeth and mouth.